Issue Management Strategy of the Special Region Government of Yogyakarta Related to the Relocation of the Abu Bakar Ali Special Parking Place - Bia Ahmad Alfarisi; Iva Fikrani Deslia (Publikasi Indonesia, 2026)
This research discusses the issue management strategy implemented by the Special Regional Government of Yogyakarta (DIY) related to the relocation of the Abu Bakar Ali Special Parking Place (TKP) in the Malioboro area. This relocation aims to rearrange the tourist area that has become an icon of Yogyakarta, reduce congestion, and support carbon emission reduction policies. The research used a descriptive qualitative approach with interviews, observations, and documentation to explore the process of identification, analysis, and response to emerging issues, including the economic concerns of traders and parking attendants, social issues, and distrust of the government. The Yogyakarta government has chosen an adaptive, responsive, and participatory issue management strategy, by adjusting policies based on community needs and providing adequate facilities in the new location. The results show that the success of relocation is highly dependent on transparent communication, community participation, and ongoing evaluation of the social and economic impacts of these policies. The issue management approach applied demonstrates the importance of collaboration between governments, communities, and other stakeholders to achieve sustainable development goals.